2016
DOI: 10.1007/s10144-016-0540-7
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity in the network macrostructure of Tursiops truncatus in the Pelagos Sanctuary (NW Mediterranean Sea): does landscape matter?

Abstract: The bottlenose dolphin (Tursiops truncatus Montagu, 1821) is a regularly observed species in the Mediterranean Sea, but its network organization has never been investigated on a large scale. We described the network macrostructure of the bottlenose dolphin (meta)population inhabiting the Pelagos Sanctuary (a wide protected area located in the north-western portion of the Mediterranean basin) and we analysed its connectivity in relation to the landscape traits. We pooled effort and sighting data collected by 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Thus, this structure is the most similar to coastal resident stocks of the Mediterranean semi-enclosed gulfs (such as the Gulf of Amvrakikos), West Atlantic estuaries or Hawaii (Speakman et al , 2006; Bearzi et al , 2008, 2011; Baird et al , 2009). It is strikingly similar to the metapopulation structure of bottlenose dolphins in the north-western Mediterranean waters (Carnabuci et al , 2016), but differs from it in looser connectivity and longer distances between local groupings. However, as opposed to these regions, there is no distinct physical or biotic factor causing isolation of dolphins in the coastal Black Sea.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, this structure is the most similar to coastal resident stocks of the Mediterranean semi-enclosed gulfs (such as the Gulf of Amvrakikos), West Atlantic estuaries or Hawaii (Speakman et al , 2006; Bearzi et al , 2008, 2011; Baird et al , 2009). It is strikingly similar to the metapopulation structure of bottlenose dolphins in the north-western Mediterranean waters (Carnabuci et al , 2016), but differs from it in looser connectivity and longer distances between local groupings. However, as opposed to these regions, there is no distinct physical or biotic factor causing isolation of dolphins in the coastal Black Sea.…”
Section: Discussionsupporting
confidence: 75%
“…For example, in Californian waters the local groupings form a metapopulation in which the inter-stock exchange rate is 43% (Defran et al , 1999; Hwang et al , 2014). However, resident stocks can also be connected within a metapopulation structure, although with higher site fidelity and lesser frequency of inter-stock movements, as in north-western and central Mediterranean areas (Bearzi et al , 2011; Gnone et al ., 2011; Carnabuci et al , 2016; Genov et al , 2016), which was also confirmed by genetic studies (Gaspari et al , 2015). Owing to such a structure with a great number of individual transfers within a metapopulation, many coastal stocks of bottlenose dolphins gain a relative sustainability in the long-term, despite their low reproductive rate (Stolen & Barlow, 2003).…”
Section: Discussionmentioning
confidence: 54%
“…This is a first study of the reproductive parameters of female bottlenose dolphins in the Mediterranean, based on a 9-year-long sighting-history data set and related photo-identification from the eastern Ligurian Sea. The studied bottlenose dolphins seem to have very little or no contact with adjacent dolphin communities in Corsica or eastern France Carnabuci et al 2016), therefore supporting the hypothesis of a partially isolated sub-population, in the specific sense of a group of animals dwelling in a determined area (Ricklefs & Miller 1999).…”
Section: Discussionsupporting
confidence: 64%
“…Several studies found spatial segregation in Tursiops (Chilvers and Corkeron 2001; Chilvers et al 2003; Lusseau et al 2006; Fury et al 2013; Carnabuci et al 2016). In Moray Firth, Scotland, this segregation appeared season-dependent (Wilson et al 1997).…”
Section: Discussionmentioning
confidence: 99%